Interior Societas - a amizade e a dialética entre interioridade e alteridade nas cartas a Lucílio de Sêneca - Tatarek, Natália Vasconcelos Rodrigues (2020)
There is no specific work on friendship in stoic thought. However, Seneca, who stands out in the imperial phase of the doctrine, in his last work Letters to Lucilius, dedicates some letters to the theme of friendship. One aspect is particularly interesting in the discussion of the concept of friendship in Seneca: the harmonization of the principle of autarky - fundamental to Stoic thought - and the relationship between friends. For Stoicism, the wise man is the one who reaches full autarky, that is, self-sufficiency. The wise man is the one who has complete control of himself (the rational soul), thus achieving inner peace, without letting himself be disturbed by anything that is external to him. The deepening of the principle of autarky in Seneca is pertinent and necessary for the understanding of friendship in his discourse because it can be seen that beyond the existence of a problematic between friendship and autarky, it is a misinterpretation of what is defined in Seneca as the happy life based on virtue. These implications present in the Senekian discourse drive the present research. The problematic of this thesis is the result of them, in which the dialectic between friendship and Stoic autarky is questioned, which, in a broader discourse, is called a dialectic between otherness and interiority. The detailed reading of the Letters to Lucilius concerning friendship and other letters of the epistolary series that help to deepen the theme reinforces our thesis of a possible harmonization of friendship and autarky within the stoic thought, specifically, in Seneca. Therefore, we intend to discuss this relationship between the phenomenon of friendship, a concrete experience found in Seneca's letters, which arises from the need to share one's own progress in wisdom with another, being the search for friendship a natural human instinct, and the achievement of the Stoic High Good, which is based on the principle of autarky of the wise man, the model for the happy Stoic life.